Economic Assessment of the Current State of the Housing and Communal Services of the Republic of Kazakhstan, Taking into Account the Influence of Foreign Experience - Batkeyeva, D.; Mataeva, B.; Saparova, B.; Kazbekov, T.; Ulakov, S. (Montenegrin Journal of Economics, 2023)
The essence of institutional housing and communal reforms is to change the elements of the institutional system, which can be carried out through legal coercion by the state or with the active participation of economic agents. The development of theoretical and methodological approaches to substantiate the mechanisms for creating an appropriate innovative environment and stimulating the innovative activity of enterprises in the housing and commu-nal services, including the construction industry, is carried out to a large ex-tent on the basis of the modernization of investment policy, taking into ac-count the economic, geographical, social, environmental and other features that make up the economic space of a country or region. In this connection, the new generation of housing and communal services at the present stage faces the task of increasing the comfort of living for the population, taking into account regional characteristics and existing trends in design based on the use of new technologies or the so-called green economy - green innova-tions. The purpose of the study is an economic analysis of the current state of the housing and communal services of the Republic of Kazakhstan, taking into account the influence of foreign experience and the identification of fac-tors affecting the environment during the construction of facilities.
Keywords: Housing and communal services; housing construction; green economy; green innovations; environment; innovations